User Management and Authentication of Hotspot Using Mikrotik Hotspot Monitor at A Coffee Shop - Gunawan Budi Sulistyo; Pudji Widodo; Noor Hasan (Publikasi Indonesia, 2024)
This research aims to analyze the effectiveness of using the Mikrotik Hotspot Monitor in user authentication management in hotspot networks. User authentication challenges that include security and ease of management motivate the use of Mikrotik to improve system efficiency. The research method used is a qualitative approach with a case study. Data collection is done through interviews with users and managers and direct observation. The results showed that Mikrotik Hotspot Monitor is able to improve the security and efficiency of authentication management. Users find this method more straightforward than other methods, such as Radius. In conclusion, Mikrotik Hotspot Monitor is an effective solution for authentication management on hotspot networks by offering features that are easy to use and efficient in supporting internet service business needs.